Mucin Level as a Potential Biomarker for Breast Cancer Diagnosis - Tagwa Sayed Abdihalim; Alkhair Abd Almahmoud Idris (Cell and BioPharmaceutical Institute, 2022)
Background: Breast cancer is the second leading cause of cancer death and a health problem worldwide. Secreted mucins are upregulated in ductal adenocarcinoma of the breast, however, the use of mucin as breast cancer biomarker has not been established before. This study aimed to determine the use of mucin level as a potential biomarker for breast cancer diagnosis. Materials and methods: This was a retrospective, cross-section study involving 40 women subjects with breast cancer. Mucin level was examined with a combination of Alcian blue/periodic acid Schiff (AB/PAS) technique applied to each specimen. The results obtained were statistically analyzed using SPSS.Results: Results of neutral mucin detection showed that among breast cancer subjects, 16 cases (40%) were neutral mucin score (+), 23 cases (57.5%) were neutral mucin score (++), and 1 case (2.5%) was neutral mucin score (+++). Meanwhile, 10 cases (25%) were acid mucin negative, 17 cases (42.5%) were acid mucin score (+), 11 cases (27.5%) were acid mucin score (++), and 2 cases (5%) were acid mucin score (+++). The most frequent type of mucin was the combination of acid and neutral mucin (30 cases; 75%) and neutral mucin were 10 cases (25%). Conclusion: Detection of mucin level can be used as an alternative technique for the diagnosis of breast cancer complementary to other types of special stains. Keywords: AB, PAS, breast cancer, histological grade, mucin level